Effectiveness of Using Kahoot As A Learning Medium in Teaching Physics on Global Warming Material for Senior High School Students - Yusuf, Mesi Riskiyanti; Iqbal, Mochamad (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
The use of technology-based learning media such as Kahoot has become increasingly popular in line with the growing need for engaging and interactive teaching methods, especially in the context of science education such as physics. Physics is a subject that contains many abstract concepts and is often considered difficult by students. Therefore, innovative approaches are needed to facilitate enjoyable conceptual understanding. Kahoot, as a game-based digital quiz platform, offers a fun and competitive alternative that can enhance students' learning motivation and active participation in the learning process. This study aims to determine the effectiveness of using Kahoot as a learning medium in teaching physics on the topic of global warming in grade X at SMA Kolombo Sleman. The research method employed is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results show that the use of Kahoot not only increases students' active participation but also strengthens their understanding of physics concepts related to global warming. In addition, students become more motivated to learn due to the competitive atmosphere and immediate feedback provided by the Kahoot application.